Pengaruh Metode Resitasi Terhadap Aktivitas Bertanya Dan Berpikir Kritis Siswa Kelas X MA Putra Al-Islahuddiny Kediri - Rida’ul Hayatin; Mukminah Mukminah; Muhammad Zulhariadi (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
This study intend the effect of the recitation method on students asking question activities and critical thinking students especially boys of class X Islamic Boarding School Al-Islahuddiny Kediri on material environmental change. This research includes quantitative research, the type of research used is quasi-experimental. The population in this study were class X students of MA Putra Al-Islahuddiny Kediri, totaling 407 students. Sampling used a purposive sampling technique, the samples in this study were 44 students in class X IPA 1 and 47 students in X IPA 2. The research design used a non-randomized control group pretest posttest design. The research instrument was in the form of essay tests and observation sheets. Analysis of the research data used a statistical test, namely Manova using SPSS 23. The results showed that there was an effect of the recitation method on students' questioning activities and then there was an effect of the recitation method on students' critical thinking. This can be seen from the results of the analysis of the Manova test on student questioning activities obtained an with Sig.0.000 and the results of students' critical thinking analysis obtained an with Sig. 0.000. Based on these data, there is an effect of the recitation method on students' questioning activities and there is an effect of the recitation method on the critical thinking of class X MA Putra Al-Islahuddiny Kediri on environmental change material.